Users Satisfaction with Services, Resources, and Facilities in Nigeria Maritime University Library Okerenkoko, Delta State - Idjai, Confidence Reghagwa (Library Philosophy and Practice (e-journal), 2023)
The aim of the study was to examine users’ satisfaction with services, resources, and facilities in Nigeria Maritime University Library Okerenkoko, Delta State. The study adopted a descriptive survey design because of its potency in examining respondents via data collection and analysis to arrive at a conclusion. The total enumeration sampling technique was adopted for the study because of the manageable size of the population. The instrument used for eliciting data from the respondents was a structured questionnaire with the aid of two research assistants. The researcher distributed 215 copies of the questionnaire to the respondents and only 206 copies were returned and found usage for the research. The elicited via the questionnaire were analysed using descriptive statistics method which involves mainly frequency counts and percentage. The findings revealed that the extent of patronage of the Nigeria Maritime University library was low as users only patronise the library for reading for examination and test. Also, it can be concluded from the findings that the users’ satisfaction level with the Nigeria Maritime University Library Services is high. The findings revealed that the users’ satisfaction level with the Nigeria Maritime University library resources is high. Similarly, the finding revealed that the users’ satisfaction level with the Nigeria Maritime University library facilities is high. It was recommended in the study that further studies should be carried out to ascertain the factors that have led to the low patronage of the Nigeria Maritime University Library Okerenkoko, Delta State and the library's administrators should maintain the high level of user satisfaction by enhancing the availability of current and relevant information resources, contemporary facilities, and appropriate services that fulfill users' requirements and expectations.
Keywords: Users’ Satisfaction; Patronage; Services; Resources; Facilities; University Library